Cost-effectiveness of thrombectomy in patients with minor stroke and large vessel occlusion: effect of thrombus location on cost-effectiveness and outcomes. (12th January 2022) - Khunte, Mihir; Wu, Xiao; Koo, Andrew; Payabvash, Seyedmehdi; Matouk, Charles; Heit, Jeremy J; Wintermark, Max; Albers, Gregory W; Sanelli, Pina C; Gandhi, Dheeraj; Malhotra, Ajay
Abstract : Background: To evaluate the cost-effectiveness of endovascular thrombectomy (EVT) to treat large vessel occlusion (LVO) in patients with acute, minor stroke (National Institute of Health Stroke Scale (NIHSS) <6) and impact of occlusion site. Methods: A Markov decision-analytic model was constructed accounting for both costs and outcomes from a societal perspective. Two different management strategies were evaluated: EVT and medical management. Base case analysis was done for three different sites of occlusion: proximal M1, distal M1 and M2 occlusions. One-way, two-way and probabilistic sensitivity analyses were performed. Results: Base-case calculation showed EVT to be the dominant strategy in 65-year-old patients with proximal M1 occlusion and NIHSS <6, with lower cost (US37 229 per patient) and higher effectiveness (1.47 quality-adjusted life years (QALYs)), equivalent to 537 days in perfect health or 603 days in modified Rankin score (mRS) 0–2 health state. EVT is the cost-effective strategy in 92.7% of iterations for patients with proximal M1 occlusion using a willingness-to-pay threshold of US100 000/QALY. EVT was cost-effective if it had better outcomes in 2%–3% more patients than intravenous thrombolysis (IVT) in absolute numbers (base case difference −16%). EVT was cost-effective when the proportion of M2 occlusions was less than 37.1%. Conclusions: EVT is cost-effective in patients with minor stroke and LVO in the long term (lifetime horizon), considering the poor outcomes and significant disability associated with non-reperfusion. Our study emphasizes the need for caution in interpreting previous observational studies which concluded similar results in EVT versus medical management in patients with minor stroke due to a high proportion of patients with M2 occlusions in the two strategies.